Seismic activity in the continental shelf of South-Central Vietnam and adjacent regions from 2005 to 2020 - Nguyen, Thi Mai; Nguyen, Hong Phuong; Vu, Van Phong; Pham, The Truyen; Bui, Thi Nhung (Vietnam Journal of Marine Science and Technology, 2022)
Since 2005, 10 seismic monitoring stations have been installed in the southern part of Vietnam. These stations can detail the earthquakes in the region and adjacent areas. In the past, there was an earthquake of magnitude 6.1 (1923) in the offshore South-Central Part related to the Hon Tro eruption, the largest observed earthquake magnitude in the 20th century. Between 2005 and 2020, 371 earthquakes were recorded with magnitudes ranging from 0.7 to 5.3. Most of events were distributed on some northeast-southwest direction faults in South Central offshore. The magnitude of the representative earthquake was relatively small, Mc = 2.2, so it is assumed that this research area was of weak activity. The epicenter is about < 20 km, and the majority concentration is at a relatively shallow depth of 5km and still located in the crust of Earth. The relationship between earthquake magnitude and frequency in this region is as follows: lgN = 4.063 – 0.694*M for the entire catalog of 371 events and lgN = 3.826 – 0.704*M after filtering 92 foreshocks and aftershocks of the earthquakes M = 5.3 on November 8th, 2005, and M = 5.2 on November 28th, 2007. So, the calculated average b-values before and after filtering foreshocks and aftershocks were approximately 0.7. These values are almost approximate to the b-value of 0.76 determined by Pham Van Thuc et al., (2004) based on the East Vietnam Sea earthquake catalog from 1903 to 2002 and smaller than the b-value of 0.92 for triggered earthquakes in the Song Tranh 2 hydropower region. In addition, oil and gas exploitation activities are still taking place in the South-Central continental shelf; it is necessary to continue collecting earthquake data to elucidate the causes of earthquakes in the study region.